2008
DOI: 10.1161/circresaha.108.187534
|View full text |Cite
|
Sign up to set email alerts
|

Notch and Vascular Smooth Muscle Cell Phenotype

Abstract: Abstract-The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
141
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 150 publications
3
141
0
2
Order By: Relevance
“…The Notch pathway has been reported to contribute to the control of the smooth muscle phenotype (Morrow et al, 2008) and implicated in the amplification of mammary myoepithelial progenitors (Dontu et al, 2004). The impact of Notch signaling on control of the balance of smooth muscle (and, probably, myoepithelial) cell proliferation and differentiation is context dependent.…”
Section: Contractile Function and The Control Of Mammary Myoepitheliamentioning
confidence: 99%
“…The Notch pathway has been reported to contribute to the control of the smooth muscle phenotype (Morrow et al, 2008) and implicated in the amplification of mammary myoepithelial progenitors (Dontu et al, 2004). The impact of Notch signaling on control of the balance of smooth muscle (and, probably, myoepithelial) cell proliferation and differentiation is context dependent.…”
Section: Contractile Function and The Control Of Mammary Myoepitheliamentioning
confidence: 99%
“…VSMC respond to vascular injury with decreased expression of contractile proteins and increased proliferation and migration (3). Several pathways have been identified that promote the VSMC contractile phenotype including SRF/myocardin (4), transforming growth factor ␤ (5, 6), and Notch signaling (7,8), while transcription factors such as Krüp-pel-like factor 5 (KLF5) are known to promote a proliferative phenotype by direct binding to the cyclin D1 promoter (9).…”
mentioning
confidence: 99%
“…Notch signaling is significantly involved in the responses of the vasculature to injury and growth stimulation (16). Jagged1, a ligand for Notch receptors, is abundantly present in Ecs.…”
Section: Discussionmentioning
confidence: 99%